Widening the Frontiers of Competition Law: The Impact of Digital Market on "our" Privacy - Memeti, Nora (كلية القانون الكويتية العالمية, 2018)
In the digital world, we exchange our privacy and personal data to access social and professional platforms, search engines etc. It is known as “take it or leave it” principle by which access to various platforms is provided in exchange for personal data. These platforms generate, gather and analyze on daily basis a huge amount of personal data. Personal data and privacy issues have fundamental and economic value and are closely related to consumers. This paper discusses the developments in the digital market and their impact on privacy and personal data in Competition Law. In particular, it analyzes how the frontiers of Competition Law can be amplified in order to address privacy and personal data rights. EU Institutions and Member States at national level have been addressing Privacy and Data Protection in the digital market based on the Primary and Secondary legislation. Moreover, there is a major development in this area of law with the shift from the Data Protection Directive to the General Data Protection Regulation (GDPR) which requires further critical review. These developments on digital and traditional markets and personal data may impact other countries and regions, including the Gulf Cooperation Council (GCC) countries."
Keywords: القدرات التنافسية -- الأسواق المالية -- التقنيات الرقمية